2014
DOI: 10.5114/pdia.2014.40924
|View full text |Cite
|
Sign up to set email alerts
|

Switching from systemic steroids to ciclesonide restores the hypothalamic pituitary-adrenal axis

Abstract: IntroductionTreatment of difficult asthma with oral corticosteroids (OCS) may suppress the hypothalamic-pituitary-adrenal axis.AimIn this study we have checked if the substitution of OCS with very high doses of ciclesonide may restore the adrenal function without losing the control of the disease.Material and methodsIn 5 patients with difficult, uncontrolled asthma despite treatment with OCS, inhaled and systemic glucocorticosteroids were replaced with very high doses of ciclesonide (1600–2400 µg/day). The sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The safety of ICS, especially when using high doses, depends on their dose, formulation and pharmacological properties. Marczak published a study in which he showed that switching from prednisone to very high doses of ciclesonide normalized the hypothalamic-pituitary adrenal axis function and also improved the disease control and the lung function in patients with difficult asthma [21].…”
Section: Discussionmentioning
confidence: 99%
“…The safety of ICS, especially when using high doses, depends on their dose, formulation and pharmacological properties. Marczak published a study in which he showed that switching from prednisone to very high doses of ciclesonide normalized the hypothalamic-pituitary adrenal axis function and also improved the disease control and the lung function in patients with difficult asthma [21].…”
Section: Discussionmentioning
confidence: 99%